2012
DOI: 10.1016/j.cell.2012.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Neuromodulation In Vivo: TANGO-Mapping of Dopamine Signaling Reveals Appetite Control of Sugar Sensing

Abstract: Due to a copyediting error, in the sentence below from the Results section of the above article, the number ''15'' was inadvertently replaced with ''150.'' A corrected version of the article now appears online.''The dynamic range of this reporter (2-to 15-fold; Figures 2B 1 -2B 4 ) is similar to that of the best currently available genetically encoded calcium indicators (GECIs) (Tian et al., 2009), although the signal-to-noise ratio (SNR; c.a. 4) is lower (see Extended Experimental Procedures).''

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 0 publications
7
85
1
Order By: Relevance
“…In fruit flies, it has been shown that starvation increases the likelihood of proboscis extension reflex (PER) to sucrose, a behavioral component of feeding initiation (39). We found that TβH M18 mutant flies showed comparable PER responses to Canton-S controls under both fed and starved conditions (Fig.…”
Section: Octopamine Is Not Required For Starvation-induced Changes Inmentioning
confidence: 55%
See 1 more Smart Citation
“…In fruit flies, it has been shown that starvation increases the likelihood of proboscis extension reflex (PER) to sucrose, a behavioral component of feeding initiation (39). We found that TβH M18 mutant flies showed comparable PER responses to Canton-S controls under both fed and starved conditions (Fig.…”
Section: Octopamine Is Not Required For Starvation-induced Changes Inmentioning
confidence: 55%
“…PER. PER was assayed as described previously (39). Briefly, sucrose-fed and starved flies were gently aspirated and mounted into Pipetman tips (200 μL).…”
Section: Methodsmentioning
confidence: 99%
“…The neural transmission of the gustatory receptor neurons that sense amino acids might be enhanced (Inagaki et al, 2012). Because the taste sensitivity to amino acids specifically increases, an alternative possibility is that deprivation induces expression of a gene or genes encoding a putative taste receptor for amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Preference for caloric sugars is potentiated by starvation Starvation is known to enhance feeding behaviors and taste sensitivity in flies (Barton Browne, 1975;Scheiner et al, 2004;Farhadian et al, 2012;Hergarden et al, 2012;Inagaki et al, 2012). To test the effects of starvation on preference for caloric sugars, we fooddeprived flies for 8 or 24 h and measured their preference for the mixture of 20% sucrose and 80% mannose versus L-fucose.…”
Section: Flies Shift Feeding Preference Toward Caloric Sugarsmentioning
confidence: 99%